Engaging depressive disengagement - Quinto, Pamela Alexis M.; Sta. Ana, Mary Catherine P.; Malto, Marco Ruben II (Quezon City College of Fine Arts, University of the Philippines Diliman, 2014)
The context of this thesis revolved around depression, particularly its conditions which I observed in my experience with a family member. The thesis inquiry that I sought to answer was: In what way can I visually depict the depressive conditions of a vegetative state, withdrawal and inwardness through an installation using clay as material? How can recorded sound be used to help describe a depressive state? I depicted the vegetative state through an ephemeral clay sculpture of a bed with a sleeping body's indentation: and installed it in the middle of a ark room with s spotlight on the sculpture. I visualized social withdrawal through the indentation's negative form and the atmosphere of isolation created through the sculpture's placement in the dark room. Inwardness was shown through audio recordings that accompanied the installation. I also depicted the fragile state of a depressed person, and represented the hope that this state will come to pass, through the temporary nature of unfired clay. In relation to depression as neurosis or mental disorder, my theoretical basis was psychoanalytical. I also referred to its concept of catharsis, the idea of art as catharsis, and used the idea of expression and expressionism, in relation to catharsis. The significance of this thesis is to concretize the conditions of depression that I encountered through my experience. I felt that art was a good medium for raising some understanding about it in viewers and other artists. This thesis is a means of opening dialogue about depression. It is also significant in terms of being a form of catharsis, of art being a release of ill feelings I have toward the state of depression, as well as a means of talking about conditions of depression.
Thesis (Bachelor of Fine Arts - Painting)--University of the Philipines Diliman
Bibliography : leaf 14.
Keywords: Depression, Mental